Editorial - Pacheco-Romero, José (2017)
Millennium Development Goal 5 calls for a 75% reduction in the maternal mortality ratio (MMR) between 1990 and 2015. Data for 171 of 183 countries indicate that the global MMR fell from 385 deaths per 100 000 live births (80% uncertainty intervals-UI 359-427) in 1990, to 216 (207-249) in 2015, corresponding to a relative decline of 43·9% (34·0-48·7), with 303 000 (291 000-349 000) maternal deaths worldwide in 2015. Accelerated progress will be required to achieve the United Nations Sustainable Development Goals (SDG); countries will need to reduce their MMRs at an annual rate of at least 7·5%(1).